Valorization of saffron (Crocus sativus L.) stigma as a potential natural antioxidant for soybean (Glycine max L.) oil stabilization - Moussa Nid Ahmed; Karima Abourat; Jamila Gagour; El Hassan Sakar; Khalid Majourhat; Jamal Koubachi; Said Gharby (Heliyon, 2024)
Synthetic antioxidants are known for their efficiency to improve vegetable oil oxidative stability. But owing to their harmful effects on human health, edible oil industry is seeking for safe and healthy natural antioxidants. The present work was setup with the aim of improving soybean oil (SO) oxidative stability by using saffron (Crocus sativus L.) stigmas collected in Morocco. Saffron stigmas were used as a natural antioxidant at various concentrations (0.2, 0.3, and 0.6%) in soybean oil compared to tocobiol (0.3%) as a synthetic antioxidant (the positive control). Performances of such natural and synthetic antioxidants were evaluated by measuring oil basic quality indices under accelerated storage at 60 °C for 12 weeks. Such indices consisted of free fatty acids (FFA), peroxide value (PV), anisidine value (p-AV), total oxidation value (TOTOX), UV extinction coefficients (K232 and K270), fatty acids composition (FA), and iodine value (IV). The obtained data show that there were significant (p < 0.05) increases in FFA, PV, p-AV, K232, K270, and TOTOX but no much variations were observed for FA and IV especially in saffron stigmas fortified oils across storage times. However, in the case of oils fortified with saffron stigmas at different doses, such an increase was of a lesser magnitude (for FFA, PV, p-AV, K270, and TOTOX) as compared to tocobiol. These outcomes were confirmed by principal component analysis with strong positive correlations (p < 0.001) among FFA, PV, p-AV, K232, K270, and TOTOX. The most important, for which determination coefficient R2 > 0.9, were modeled through simple regressions. In conclusion, saffron stigmas with the different doses performed better than the positive control (tocobiol) regardless of the storage time. It could be concluded that saffron stigmas are a promising natural antioxidant, alternative to synthetic antioxidants, to enhance the oxidative stability of edible oils.